Profiles of 5α-Reduced Androgens in Humans and Eels: 5α-Dihydrotestosterone and 11-Ketodihydrotestosterone Are Active Androgens Produced in Eel Gonads - Yazawa, Takashi; Inaba, Hiroyuki; Imamichi, Yoshitaka; Sekiguchi, Toshio; Uwada, Junsuke; Islam, Mohammad Sayful; Orisaka, Makoto; Mikami, Daisuke; Ida, Takanori; Sato, Takahiro; Miyashiro, Yoshimichi; Takahashi, Satoru; et al. (Frontiers in Endocrinology, 2021)
Although 11-ketotestosterone (11KT) and testosterone (T) are major androgens in both teleosts and humans, their 5alpha-reduced derivatives produced by steroid 5alpha-reductase (SRD5A/srd5a), i.e., 11-ketodihydrotestosterone (11KDHT) and 5alpha-dihydrotestosterone (DHT), remains poorly characterized, especially in teleosts. In this study, we compared the presence and production of DHT and 11KDHT in Japanese eels and humans. Plasma 11KT concentrations were similar in both male and female eels, whereas T levels were much higher in females. In accordance with the levels of their precursors, 11KDHT levels did not show sexual dimorphism, whereas DHT levels were much higher in females. It is noteworthy that plasma DHT levels in female eels were higher than those in men. In addition, plasma 11KDHT was undetectable in both sexes in humans, despite the presence of 11KT. Three srd5a genes (srd5a1, srd5a2a and srd5a2b) were cloned from eel gonads. All three srd5a genes were expressed in the ovary, whereas only both srd5a2 genes were expressed in the testis. Human SRD5A1 was expressed in testis, ovary and adrenal, whereas SRD5A2 was expressed only in testis. Human SRD5A1, SRD5A2 and both eel srd5a2 isoforms catalyzed the conversion of T and 11KT into DHT and 11KDHT, respectively, whereas only eel srd5a1 converted T into DHT. DHT and 11KDHT activated eel androgen receptor (ar)-mediated transactivation as similar fashion to T and 11KT. In contrast, human AR and eel ar were activated by DHT and11KDHT more strongly than T and 11KT. These results indicate that in teleosts, DHT and 11KDHT may be important 5alpha-reduced androgens produced in the gonads. In contrast, DHT is the only major 5alpha-reduced androgens in healthy humans.